The identification of research priorities for UK occupational therapists in work rehabilitation - Coole, Carol; McBean, Juliet; Drummond, Avril E.R. (Mark Allen Healthcare, 2015)
Background/Aims: UK occupational therapists are recognised as having key skills in work rehabilitation, but there is limited evidence to underpin this. In order to use research resources to best effect, it is vital to identify the research priorities of occupational therapists in work rehabilitation. This study aims to gather the views of those with a special interest in the field in order to identify their research priorities.